2006
DOI: 10.1017/s0033822200038789
|View full text |Cite
|
Sign up to set email alerts
|

How to Convert Biological Carbon Into Graphite for AMS

Abstract: Isotope tracer studies, particularly radiocarbon measurements, play a key role in biological, nutritional, and environmental research. Accelerator mass spectrometry (AMS) is now the most sensitive detection method for radiocarbon, but AMS is not widely used in kinetic studies of humans. Part of the reason is the expense, but costs would decrease if AMS were used more widely. One component in the cost is sample preparation for AMS. Biological and environmental samples are commonly reduced to graphite before the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(77 citation statements)
references
References 15 publications
1
76
0
Order By: Relevance
“…Under these conditions, reduction time was not a significant factor and the previous method(15) needed 6 h (abscissa broken rectangle). But we confirmed that 3 h was optimal (abscissa solid rectangle) based on the uniformity of the graphite coat when CO 2 was reduced at 500 °C (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…Under these conditions, reduction time was not a significant factor and the previous method(15) needed 6 h (abscissa broken rectangle). But we confirmed that 3 h was optimal (abscissa solid rectangle) based on the uniformity of the graphite coat when CO 2 was reduced at 500 °C (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…(7) On the other hand our optimized CO 2 reduction method formed only GCIP (black, soft powder, uniform, fuzz) 100% of the time. (13) In general, the presence of a nongraphitic carbon or Fe 3 C crystal resulted in the formation of a harder carbon structure than a compact graphitized carbon.…”
Section: Discussionmentioning
confidence: 99%
“…HPLC fractions were collected, dried and converted to graphite as previously described (Buchholz et al, [2000]; Getachew et al, [2006]; Miyashita et al, [2001]). 14 C contents in the graphite samples were quantified by AMS (Ognibene et al, [2002]).…”
Section: Methodsmentioning
confidence: 99%